Transnational Mobiles in Bhramar and Dak Bangala - Timalsina, Ramji (Dristikon: A Multidisciplinary Journal, 2024)
This article has discussed the Nepali transnational mobiles as the characters in two of the early Nepali novels written by the Indian Nepali novelists. In the early twentieth century when India referred to British India that covered present India, Bangladesh, Pakistan and Myanmar (Burma), Nepali people used to migrate there in search of works and opportunities. When they left home, they thought to return after certain earnings. But the life was not so easy, and finally most of them stranded in life never to reach anywhere. Rupnarayan Singh’s Bhramar (1970/1936) and Shivakumar Rai’s Dak bangala (2020/1957) have used such Nepali transnational mobiles as the characters. These characters have always been found in the transition as they are wanderers without any fixed place to settle and feel the peace of mind. Mobility is their common quality. The analysis has been based on Janine Dahinden and Steven Vertovec’s idea of transnationalism. They have termed the cross-border migrants who never get permanently settled in the hostland as the transnational mobiles. This article has picked up such characters from both of the novels and discussed their life, culture, mentality and conditions of existence. This article can be a sample for further analysis of Nepali novels from transnational perspective.